On second thought … the influence of a second stage in the ultimatum game on decision behavior, electro‐cortical correlates and their trait interrelation. (17th February 2022) - Rodrigues, Johannes; Weiß, Martin; Mussel, Patrick; Hewig, Johannes
Abstract: Previous EEG research only investigated one stage ultimatum games (UGs). We investigated the influence of a second bargaining stage in an UG concerning behavioral responses, electro‐cortical correlates and their moderations by the traits altruism, anger, anxiety, and greed in 92 participants. We found that an additional stage led to more rejection in the 2‐stage UG (2SUG) and that increasing offers in the second stage compared to the first stage led to more acceptance. The FRN during a trial was linked to expectance evaluation concerning the fairness of the offers, while midfrontal theta was a marker for the needed cognitive control to overcome the respective default behavioral pattern. The FRN responses to unfair offers were more negative for either low or high altruism in the UG, while high trait anxiety led to more negative FRN responses in the first stage of 2SUG, indicating higher sensitivity to unfairness. Accordingly, the mean FRN response, representing the trait‐like general electrocortical reactivity to unfairness, predicted rejection in the first stage of 2SUG. Additionally, we found that high trait anger led to more rejections for unfair offer in 2SUG in general, while trait altruism led to more rejection of unimproving unfair offers in the second stage of 2SUG. In contrast, trait anxiety led to more acceptance in the second stage of 2SUG, while trait greed even led to more acceptance if the offer was worse than in the stage before. These findings suggest, that 2SUG creates a trait activation situation compared to the UG. Abstract : Previous EEG research considered one stage ultimatum games (UG). We compared a 2‐stage Ultimatum Game (2SUG) with UG. We found more initial rejection, acceptance for increasing offers as well as more pronounced trait influence on behavior and electrophysiology in 2SUG. The FRN during trials was linked to expectancy (fairness) evaluation, while midfrontal theta (N3) expressed cognitive control to overcome default behavior. Also, trait‐like more negative FRN amplitudes indicated sensitivity for unfairness by predicting higher rejection rates.